PENGARUH CSR TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Milayati, Depi; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research examines the influence of Corporate Social Responsibility to the firm value with financial performance which is measured by using Return on Asset as the intervening variable on manufacturing companies which are listed in Indonesia Stock Exchange. The companies which have been selected as samples in this research is the manufacturing companies in the food and beverages sector which are listed in Indonesia Stock Exchange in 2011-2013 periods. The sample collection has been done by using purposive sampling method and the sample selection which is based on the determined criteria and 10 companies have been selected as samples. The data analysis technique is two-stage regression analysis. The purpose of this research is used as the consideration in order to gain information about the involvement of Corporate Social Responsibility, financial performance, and firm value and to find out how great the advantage of social disclosure which is useful for the company and the stakeholders. The result of the research shows that Corporate Social Responsibility has an influence to the firm value whereas the financial performance is the intervening variable between Corporate Social Responsibility and firm value.Keywords: Corporate Social Responsibility, Return on Asset, and firm value